CHARACTERISTICS OF CLINICAL PICTURE AND BIOLOGIC FEATURES OF RARE BREAST CANCER FORMS - G. V. Martinova; I. V. Visotskaya; V. P. Letyagin; V. D. Yermilova; Ye. A. Kim (Опухоли женской репродуктивной системы)
Low incidence and difficulties of histological type identification of rare breast cancer forms preoperatively renders paramount importance to the detailed study of all cases revealed. Within the bounds of the research which is under the way in our center, we carried out an analy- sis of patients’ records treated in the N.N. Blokhin Russian Cancer Research Center from 1985 to 2005. Overall, 1053 cases of rare breast cancer forms were diagnosed including 364 patients with tubular, 231 — mucous, 190 — medullar, 126 — papillary and 142 — metaplas- tic carcinomas. The article discusses the issues of clinical course, presentation, treatment and prognosis of rare forms of breast cancer.